Impact of the reduction of calcineurin inhibitors on renal function in heart transplant patients: a systematic review and meta‐analysis. (July 2014) - Cornu, Catherine; Dufays, Christophe; Gaillard, Ségolène; Gueyffier, François; Redonnet, Michel; Sebbag, Laurent; Roussoulières, Ana; Gleissner, Christian A.; Groetzner, Jan; Lehmkuhl, Hans B.; Potena, Luciano; Gullestad, Lars; et al.
<x xml:space="preserve">Abstract</x> Aims Calcineurin inhibitors (CNIs) taken after heart transplantation lead to excellent short‐term outcomes, but long‐term use may cause chronic nephrotoxicity. Our aim was to identify, appraise, select and analyse all high‐quality research evidence relevant to the question of the clinical impact of CNI‐sparing strategies in heart transplant patients. Methods We carried out a systematic review and meta‐analysis of randomized controlled trials on CNI reduction in heart transplant recipients. Primary outcomes were kidney function and acute rejection after 1 year. Secondary outcomes included graft loss, all‐cause mortality and adverse events. Results Eight open‐label studies were included, with 723 patients (four tested de novo CNI reduction and four maintenance CNI reduction). Calcineurin inhibitor reduction did not improve creatinine clearance at 12 months 5.46 [−1.17, 12.03] P = 0.32 I2 = 65.4%. Acute rejection at 12 months (55/360 vs. 52/332), mortality (18/301 vs. 15/270) and adverse event rates (55/294 vs. 52/281) did not differ between the low‐CNI and standard‐CNI groups. There was significant benefit on creatinine clearance in patients with impaired renal function at 6 months [+12.23 (+5.26, +18.82) ml min−1, P = 0.0003] and at 12 months 4.63 [−4.55, 13.82] P = 0.32 I2 = 75%. Conclusions This meta‐analysis did not demonstrate a favourable effect of CNI reduction on kidney function, but there was no increase in acute rejection. To provide a better analysis of the influence of CNI reduction patterns and associated treatments, a meta‐analysis of individual patient data should be performed.